A stereological analysis of the effect of early postnatal ethanol exposure on neuronal numbers in rat dentate gyrus - Miki, Takanori (Image analysis and stereology, 2000)
Maternal ethanol ingestion during pregnancy can cause fetal alcohol syndrome (FAS) in their offspring. Among the symptoms of FAS, damage to the central nervous system has emerged as one of the most serious problems. We have previously shown that a relatively high dose of ethanol exposure during early postnatal life can cause alterations in spatial learning ability. This abilityis controlled, at least in part, by the hippocampal formation. The purpose of the present study was to determine whether exposure of rat pups to ethanol during early postnatal life had effects on the total number of the dentate gyrus neurons. Wistar rats were exposed to a relatively high daily dose of ethanol between postnatal days 10 to 15. Ethanol exposure was achievedby placing rat pups in a chamber containing ethanol vapour for 3 h a day. The blood ethanol concentration was found to be about 430 mg/dl at the end of the exposure period. Groups of ethanol treated (ET), separation controls (SC) and mother reared controls (MRC) were anaesthetised and killed at 16-days-of-age by perfusion with phosphate-buffered 2.5% glutaraldehyde. The Cavalieri principle was used to determine the volume of subdivisions of the dentate gyrus, and the physical disector method was used to estimate the numerical densities of neurons within each subdivision. The total number of neurons was calculated by multiplying estimates of the numerical density with the volume. There was, on average, about 421,000 granule cells in all three treatment groups. In the hilus region, ET rats had about 27,000 neuronal cells. This value was significantly smaller than the average of 38,000 such neurons estimated to be present in both MRC and SC animals. (Abstract truncated at 2000 characters)
Keywords: Fetal alcohol syndrome; stereologija; nevroni; Hippocampus; Anatomy and histology; zarodek; embryo; alkohol; Neurons; Drug effects; podgane; histologija; Alcohol, ethyl; Adverse effects; Blood; Rats; Histological techniques; Spatial behavior; Body weight